Respuesta :

Answer:

4. The equation of the perpendicular bisector is y = [tex]\frac{3}{4}[/tex] x - [tex]\frac{1}{8}[/tex]

5. The equation of the perpendicular bisector is y = - 2x + 16

6. The equation of the perpendicular bisector is y = [tex]-\frac{3}{2}[/tex] x + [tex]\frac{7}{2}[/tex]

Step-by-step explanation:

Lets revise some important rules

  • The product of the slopes of the perpendicular lines is -1, that means if the slope of one of them is m, then the slope of the other is [tex]-\frac{1}{m}[/tex] (reciprocal m and change its sign)
  • The perpendicular bisector of a line means another line perpendicular to it and intersect it in its mid-point
  • The formula of the slope of a line is [tex]m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}[/tex]
  • The mid point of a segment whose end points are [tex](x_{1},y_{1})[/tex] and [tex](x_{2},y_{2})[/tex] is [tex](\frac{x_{1}+x_{2}}{2},\frac{y_{1}+y_{2}}{2})[/tex]
  • The slope-intercept form of the linear equation is y = m x + b, where m is the slope and b is the y-intercept

4.

∵ The line passes through (7 , 2) and (4 , 6)

- Use the formula of the slope to find its slope

∵ [tex]x_{1}[/tex] = 7 and [tex]x_{2}[/tex] = 4

∵ [tex]y_{1}[/tex] = 2 and [tex]y_{2}[/tex] = 6

∴ [tex]m=\frac{6-2}{4-7}=\frac{4}{-3}[/tex]

- Reciprocal it and change its sign to find the slope of the ⊥ line

∴ The slope of the perpendicular line = [tex]\frac{3}{4}[/tex]

- Use the rule of the mid-point to find the mid-point of the line

∴ The mid-point = [tex](\frac{7+4}{2},\frac{2+6}{2})[/tex]

∴ The mid-point = [tex](\frac{11}{2},\frac{8}{2})=(\frac{11}{2},4)[/tex]

- Substitute the value of the slope in the form of the equation

∵ y = [tex]\frac{3}{4}[/tex] x + b

- To find b substitute x and y in the equation by the coordinates

   of the mid-point

∵ 4 = [tex]\frac{3}{4}[/tex] × [tex]\frac{11}{2}[/tex] + b

∴ 4 = [tex]\frac{33}{8}[/tex] + b

- Subtract  [tex]\frac{33}{8}[/tex] from both sides

∴ [tex]-\frac{1}{8}[/tex] = b

∴ y = [tex]\frac{3}{4}[/tex] x - [tex]\frac{1}{8}[/tex]

The equation of the perpendicular bisector is y = [tex]\frac{3}{4}[/tex] x - [tex]\frac{1}{8}[/tex]

5.

∵ The line passes through (8 , 5) and (4 , 3)

- Use the formula of the slope to find its slope

∵ [tex]x_{1}[/tex] = 8 and [tex]x_{2}[/tex] = 4

∵ [tex]y_{1}[/tex] = 5 and [tex]y_{2}[/tex] = 3

∴ [tex]m=\frac{3-5}{4-8}=\frac{-2}{-4}=\frac{1}{2}[/tex]

- Reciprocal it and change its sign to find the slope of the ⊥ line

∴ The slope of the perpendicular line = -2

- Use the rule of the mid-point to find the mid-point of the line

∴ The mid-point = [tex](\frac{8+4}{2},\frac{5+3}{2})[/tex]

∴ The mid-point = [tex](\frac{12}{2},\frac{8}{2})[/tex]

∴ The mid-point = (6 , 4)

- Substitute the value of the slope in the form of the equation

∵ y = - 2x + b

- To find b substitute x and y in the equation by the coordinates

   of the mid-point

∵ 4 = -2 × 6 + b

∴ 4 = -12 + b

- Add 12 to both sides

∴ 16 = b

∴ y = - 2x + 16

The equation of the perpendicular bisector is y = - 2x + 16

6.

∵ The line passes through (6 , 1) and (0 , -3)

- Use the formula of the slope to find its slope

∵ [tex]x_{1}[/tex] = 6 and [tex]x_{2}[/tex] = 0

∵ [tex]y_{1}[/tex] = 1 and [tex]y_{2}[/tex] = -3

∴ [tex]m=\frac{-3-1}{0-6}=\frac{-4}{-6}=\frac{2}{3}[/tex]

- Reciprocal it and change its sign to find the slope of the ⊥ line

∴ The slope of the perpendicular line = [tex]-\frac{3}{2}[/tex]

- Use the rule of the mid-point to find the mid-point of the line

∴ The mid-point = [tex](\frac{6+0}{2},\frac{1+-3}{2})[/tex]

∴ The mid-point = [tex](\frac{6}{2},\frac{-2}{2})[/tex]

∴ The mid-point = (3 , -1)

- Substitute the value of the slope in the form of the equation

∵ y = [tex]-\frac{3}{2}[/tex] x + b

- To find b substitute x and y in the equation by the coordinates

   of the mid-point

∵ -1 = [tex]-\frac{3}{2}[/tex] × 3 + b

∴ -1 = [tex]-\frac{9}{2}[/tex] + b

- Add  [tex]\frac{9}{2}[/tex]  to both sides

∴ [tex]\frac{7}{2}[/tex] = b

∴ y = [tex]-\frac{3}{2}[/tex] x + [tex]\frac{7}{2}[/tex]

The equation of the perpendicular bisector is y = [tex]-\frac{3}{2}[/tex] x + [tex]\frac{7}{2}[/tex]